2000
DOI: 10.1128/iai.68.3.1687-1691.2000
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Surface Layer Proteins of Campylobacter fetus subsp. fetus in Ovine Abortion

Abstract: The role of the surface (S)-layer proteins of Campylobacter fetus subsp. fetus has been investigated using an ovine model of abortion. Wild-type strain 23D induced abortion in up to 90% of pregnant ewes challenged subcutaneously. Isolates recovered from both dams and fetuses expressed S-layer proteins with variable molecular masses. The spontaneous S-layer-negative variant, strain 23B, neither colonized nor caused abortions in pregnant ewes. A series of isogenic sapA and recA mutants, derived from 23D, also we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(78 citation statements)
references
References 32 publications
3
74
1
Order By: Relevance
“…These antigens of C. fetus, including the high molecular weight proteins of 98 to 100, 127 and 149 kDa are present in glycine extracts from C. fetus strains and the diversity of size and structure of the SLP of C. fetus have been well reported (Pei et al 1988;Fujimoto et al 1991;Brooks et al 2002). Grogono-Thomas et al (2000) reported also that most C. fetus subsp. fetus isolates from natural ovine infections express the 97 kDa protein but the 127 kDa and 149 kDa surface layer proteins are rarely seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These antigens of C. fetus, including the high molecular weight proteins of 98 to 100, 127 and 149 kDa are present in glycine extracts from C. fetus strains and the diversity of size and structure of the SLP of C. fetus have been well reported (Pei et al 1988;Fujimoto et al 1991;Brooks et al 2002). Grogono-Thomas et al (2000) reported also that most C. fetus subsp. fetus isolates from natural ovine infections express the 97 kDa protein but the 127 kDa and 149 kDa surface layer proteins are rarely seen.…”
Section: Discussionmentioning
confidence: 99%
“…Sera from rabbits immunized with C. jejuni reacted with a number of components in outer-membrane protein preparations and differed from human sera (Nachamkin and Hart 1985). Recently, an investigation has been reported on the role of S layer protein (SLP) during C. fetus infection in sheep (Grogono-Thomas et al 2000). Different isotypes of antibodies directed against SLPs during ovine infection were also demonstrated with enzyme-immunoassay (Grogono- Thomas et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sheep, Grogono-Thomas et al(2000) suggested that the 97 kDa protein of the S layer is essential for the colonization and passage of C. fetus subsp. fetus through the placenta, but that it is not directly responsible for fetal injury.…”
Section: Jejunimentioning
confidence: 99%
“…Such recombination may be site specific (21,29,35,54) or may involve repetitive (homologous) DNA sequences (55, 56). Most high-frequency DNA inversions involve site-specific recombination (1,21,29,35,36,71).Campylobacter fetus is a spiral gram-negative microaerophilic bacterial pathogen that interferes with reproductive function in ungulates and can cause extraintestinal infections in humans (28,32,46,59). C. fetus cells are covered by a paracrystalline surface array composed of specialized surface layer proteins (SLPs), ranging in size from approximately 97 to 149 kDa (14, 47).…”
mentioning
confidence: 99%